Differences in countermovement vertical jump force-time metrics between starting and non-starting professional male basketball players - Cabarkapa, Dimitrije; Cabarkapa, Damjana V.; Aleksic, Jelena; Philipp, Nicolas M.; Scott, Angeleau A.; Johnson, Quincy R.; Fry, Andrew C. (Frontiers in Sports and Active Living, 2023)
With force plates being widely implemented for neuromuscular performance assessment in sport-specific settings and various force-time metrics being able to differentiate athletes based on their performance capabilities, the purpose of the present study was to examine the differences in countermovement vertical jump (CVJ) characteristics between starting and non-starting professional male basketball players (e.g., ABA League). Twenty-three athletes (height = 199.2 ± 7.7 kg, body mass = 94.2 ± 8.2 kg, age = 23.8 ± 4.9 years) volunteered to participate in the present investigation. Upon completion of a standardized warm-up protocol, each athlete performed three maximal-effort CVJs without an arm swing while standing on a uni-axial force plate system sampling at 1,000 Hz. Independent t-tests were used to examine statistically significant differences (p < 0.05) in each force-time metric between starters (n = 10) and non-starters (n = 13). No significant differences in any of the CVJ force-time metrics of interest were observed between the two groups, during both the eccentric and concentric phases of the movement (i.e., impulse, duration, peak velocity, and mean and peak force and power). Moreover, starters and non-starters demonstrated similar performance on CVJ outcome (e.g., jump height) and strategy metrics (e.g., countermovement depth). Overall, these findings suggest that at the professional level of play, the ability to secure a spot in the starting lineup is not primarily determined by the players' CVJ performance characteristics.